Movement performance and movement difficulties in typical school-aged children. - Rujira Jaikaew; Nuntanee Satiansukpong (PLoS ONE)
Introduction Developmental Coordination Disorder (DCD) is an impairment of executive motor skills. Children aged 7-10 years gradually develop effective movement that enables smooth performance in various daily self-care, academic and sport activities. The purpose of this study was to examine whether the Movement Assessment Battery for Children-Second Edition-Age Band 2, (MABC2-AB2), which is a western standardized test, could be used in Thai children for differentiating between movement performance and movement difficulties. Method Three hundred and sixty typical Thai children aged 7-10 years old were recruited from three primary schools in Chiang Mai district, Thailand. The participants were divided into four age groups and tested using the Movement Assessment Battery for Children-Second Edition-Age Band 2-Thai version (MABC2-AB2-T). Results Manual Dexterity, Aiming and Catching, and Balance rose with age increment. Older participants had better movement performance than younger ones. The results showed that 91.11 percent of the participants had typical movement, while 3.61 and 5.28 percent of them had movement difficulty and movement at risk, respectively. In addition, three test items: Drawing Trail, Walking Heel to Toe Forward, and Hopping on Mats had a ceiling effect when used for Thai children. Conclusion The MABC2-AB2-T could be used to assess movement performance and movement difficulties in Thai children. About 9 percent of typical Thai children aged 7-10 years old needed early intervention. Administration of the three test items may need to be revised.